Hate Crimes and Race-Based Trauma on Latinx Populations: A Critical Review of the Current Research. (July 2022) - Lockwood, Sarah; Cuevas, Carlos A.
Traditionally, the literature has sought to understand the impact of racial minority status and trauma as it relates to interpersonal violence, domestic violence, and sexual assault. What has not been as extensively reviewed and summarized is how racially or ethnically motivated hate crimes impact the mental health of minorities—particularly Latinx/Hispanic groups. This review aims to summarize the current body of literature on the intersection of race-motivated hate crime and trauma responses within Latinx community. To do so, the theoretical foundation for this inquiry will build from a race-based trauma perspective. Specifically, this review connects existing frameworks for race and trauma and integrates literature that examines Latinx or Hispanic populations that have experienced discrimination, bias, or hate crime as a result of their identity or perceived identity. The importance of situating bias or hate events within the trauma literature stems from a lack of overall formal evaluation of these events, and how these occurrences are historically overlooked as a traumatic stressor. The findings of this review suggest that (1) experiencing racially motivated victimization can cause adverse mental and physical health outcomes in Latinxs and (2) currently, there is only one study that has examined the impact of hate crime on Latinxs in the United States. This leaves the field with unanswered questions about the impact of hate crime victimization among Latinxs, which is an ever-growing area in need of attention.